Family Support Strategies in Improving The Quality of Life in Elderly People With Dementia - Saifulah, Dedi; Sakinah, Mutiara; Saputro, Heri; Sutrisno, Joko (Griya Eka Sejahtera, 2025)
Background: Dementia is a progressive cognitive disorder that impacts the quality of life of the elderly, causing decreased cognitive and social functions and increased dependency. Families play an important role in providing emotional, physical, social and economic support, but not all have sufficient understanding in caring for the elderly with dementia. Lack of family knowledge and skills in caring for the elderly with dementia can cause stress for caregivers and reduce the quality of life of the elderly themselves. The Alzi Surabaya Community acts as a forum for education and assistance for families to improve optimal care. This study aimed to analyze family support strategies in improving the quality of life of the elderly with dementia in the Alzi Surabaya community.Methods: This study uses a qualitative approach with a phenomenological method. Informants were selected through purposive sampling of seven families of caregivers of the elderly with dementia. Data collection was carried out through in-depth interviews and documentation, analyzed using data reduction techniques, data presentation and drawing conclusions/verification. Data validity was tested by source triangulation.Results: The results of the study from seven respondents showed that family support plays a crucial role in improving the quality of life of the elderly with dementia. Emotional support in the form of good attention and communication improves the psychological well-being of the elderly. Physical support such as assistance in self-care and providing nutritious food, maintains the health of the elderly. Economic support ensures access to health services. In addition, family involvement in social activities also helps maintain the emotional stability of the elderly. Interaction with the Alzi Surabaya community helps families in communication strategies, managing behavioral changes and strengthening social support.Conclusion: Based on the results of the study, it was concluded that the better the family support that has been given in caring for the elderly with dementia, the better their quality of life will be